On photosynthesis and polar bears - Pade, Christian (Ökologisches Wirtschaften - Fachzeitschrift, 2007)
As opposed to humankind, plants and animals rely completely on one kind of renewable energy: the sun’s solar radiation. Biomimetic concepts mimic nature’s energy system and may thus contribute to sustainability.
Keywords: Biomimetic technologies; sustainable energy system; photosynthesis